OPTIMASI SUHU ANNEALING PROSES PCR AMPLIFIKASI GEN shv BAKTERI Escherichia coli PASIEN ULKUS DIABETIK - ., Kiki Amanda (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Escherichia coli bacteria produce Extended Spectrum Beta Lactamase (ESBLs) tohydrolyze beta lactam ring from beta-lactam antibiotics. One of the ESBLs coding genesresponsible for resistance is the shv or sulphydryl variable. Annealing temperature optimizationin the Polymerase Chain Reaction (PCR) process was carried out aimed at the success inamplifying shv genes from E. coli bacteria. The method used in in vitro-based molecular testinguses DNA Extraction Kit, PCR amplification and electrophoresis. The annealing temperature usedfor pasting primer shv 5 'GGTTATGCGTTATATTCGCC 3' and reverse shv 5 primer'TTAGCGTTGCCAGTGCTC 3' are 50 ° C, 54 ° C, 56 ° C, 57 ° C, 60 ° C and 62 ° C.Visualization of the results of the amplification using a UV lamp at a wavelength of 254 nm didnot produce an amplicon with a size of 867 bp. The conclusion of this study shows that theannealing temperature used is not yet optimum to identify shv genes from E. coli bacterial isolatesin diabetic ulcer patients who are resistant to antibiotics.